Kearifan Lokal Tradisi Kuru We Fohon Sebagai Warisan Budaya pada Suku Nonot Forenain di Desa Babulu Kecamatan Kobalima Kabupaten Malaka - Fatima Restiana Muti; Antonius Bere; Yuditha Sofiana Kofi; Clotilde Seran (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe the process of implementing the Kuru We Fohon Ceremony and to describe the deep meaning contained in the Ritual. The method in this study uses a qualitative method. This Qualitative Approach also aims to gain understanding and describe a complex reality. In qualitative, this research procedure produces descriptive data in the form of written or spoken words based on the behavior of the object being studied. The results of the study are in the form of the first planning stage: the tribal chief will gather all Lulik Atan to plan when the Kuru We Fohon Tradition (taking sacred water) will be carried out. While the implementation stage includes Halaku We Fohon (Renewal) by the tribal chief and other traditional leaders, Kuru We Fohon (Taking Sacred Water) by the tribal chief and brought by one of the traditional leaders into the traditional house, Hatama We Fohon (Giving Entering Sacred Water) the officer who brings the Sacred Water into the traditional house. in the final stage, sprinkling the traditional house using sacred water and distributing Betel Nut (mama rai) to all the Nonot Forenain tribal people. The Kuru We Fohon ritual is deeply sacred, encompassing respect for ancestors and seeking their blessings. This ritual serves not only as a means of strengthening the relationship between ancestors and humans, but also as a means of strengthening cultural values. It teaches the importance of mutual cooperation, courtesy, and morality in social life.